3. APU STARTER MOTOR RELIABILITY ANALYSIS P/N 2704506 – 4 AIRBUS A320S USING WEIBULL DISTRIBUTION AND FAILURE MODE AND EFFECT ANALYSIS AT PT INDONESIA AIRASIA - Yogi Prisma; Caesar Pradewa; Feti Fatonah; Djoko Herwanto; Desiana Putri; Muchammad Furqon; Suroso; Dikasitama (Jurnal TNI Angkatan Udara, 2026)
This study aims to determine the reliability value and failure characteristics ofthe APU starter motor P/N 2704506-4, as well as to identify the failure mode qualitatively toprovide improvement recommendations for PT Indonesia AirAsia. The starter motor in theauxiliary power unit (APU) is a vital component that functions to start the operating cycle.The method used is a mixed method, with quantitative analysis through processing historicaltime to failure data from 20 unscheduled removal cases using the Weibull distribution, andqualitative analysis through failure mode and effect analysis. Data were obtained from theAircraft Maintenance Manual, Component Maintenance Manual, and semi-structuredinterviews with engineers. The analysis results show a value of β = 2.029 (β>1) whichindicates a wear-out failure pattern. The scale parameter η recorded 3,095.71 flight hourswith a mean time to failure of 2,742.85 hours. Reliability projections show that at 2,800 hours,reliability drops to 44.23% with a failure probability of 55.77%. The FMEA analysis identifiedthree failure modes: brush wear, terminal winding burn, and oil contamination. Of these,brush wear was the dominant failure mode, with 12 cases and the highest RPN value (252).The study concluded that starter motor failure is predictive and dominated by brush wear.The primary recommendation is to transition to a preventive maintenance strategy throughvisual inspection of brush wear indicators and scheduled replacement at 2,500–2,600 flighthours to reduce unscheduled removals and increase aircraft availability.